Efektivitas Penggunaan Mutaba’ah Amal Yaumiyah Dalam Memonitoring Disiplin Ibadah Siswa Sdit Cahaya Robbani Kepahiang - Eni Sunarti; Nur Jannah (Yayasan Darusssalam Bengkulu, 2025)
Schools have a value that teaches positive values ​​and good behavior towards students, especially Islamic Religious Education subjects. In teaching at school, the practice of religious teachings in Islamic Religious Education is very important, because students are not only required to just know, memorize, also master the material in learning, but students are also required to be accustomed to practicing both when they are with the teacher or away from the teacher. Therefore, SDIT Cahaya Robbani Kepahiang uses mutabaah amal yaumiyah to monitor students' daily worship discipline. The use of Mutaba'ah Amal Yaumiyah aims to enable SDIT Cahaya Robbani Kepahiang to monitor, improve and familiarize students with worship. So that students will get used to carrying out worship (obligatory and sunnah prayers, recitations of the Koran, and infaq alms) wherever they are. This research uses a descriptive method with a qualitative approach, which produces data in the form of the use of mutabaah amal yaumiyah in monitoring student worship discipline and also to determine the effectiveness of the use of mutabaah amal yaumiyah in monitoring student worship discipline.